Authors in court scenes from the theater of copyright - Rose, Mark, 1939- (Harvard University Press, 2016)
"Authors in Court : Scenes from the Theater of Copyright examines a series of famous English and American law cases in which a prominent author or artist sues or is sued for copyright infringement. Each chapter is an exploration of the drama of authorship as it has played out on the stage of the law. Some authors strut their roles. Napoleon Sarony, for example, the celebrated New York photographer whose landmark Supreme Court case established copyright protection for photography, was fond of marching along Broadway in the 1880s costumed in a red fez and high-top campaign boots. Others, the reclusive J.D. Salinger, for example, enact their dramas precisely by shrinking from attention. Through vivid portraits of these and other figures, including Daniel Defoe, Alexander Pope, Harriet Beecher Stowe, Ann Nichols, and Jeff Koons, Authors in Court provides a narrative of two mutually interacting institutions, authorship and the law, as they develop over the course of some three hundred years of cultural and legal history. In the process, the study exposes evolving tensions between gentility and commerce, gender and professionalism, and privacy and publicity. It demonstrates how the resolution of controversies involving allegations of infringement frequently depends upon informed literary and critical analysis, and that this in turn depends upon grappling with difficulties inherent in the very notion of intellectual property"--Publisher's information.